Pengaruh Metode Pembelajaran Questions Students Have (QSH) terhadap Hasil Belajar Teknologi Informasi dan Komunikasi (TIK) Siswa Kelas VIII SMP Negeri 1 Sukasada Tahun Ajaran 2012/ 2013 - Santra, Wayan; Eka Damayanthi, Luh Putu; Mahendra Darmawiguna, I Gede; Gede Sunarya, I Made (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
The purpose of this study was to determine whether there were differences in Information Communication Technology (ICT) learning outcomes between the groups of students who were taught by using Questions Students Have learning methods and a group of students who were taught by using conventional methods. This was a quasi-experimental study and the non equivalent post- test only control group was used as the design. The population of this study was the entire students of SMP Negeri 1 Sukasada in the academic year of 2012/2013. The total sample used in this study was 67 students. These samples were taken from VIII.H class as the experimental group and VIII.G class as the control group. The data of studentsâ€™ learning outcome was collected using a multiple-choice test method for measuring the cognitive, and then it was analyzed by conducting precondition test which included normality test and homogeneity test, t-test. Based on the data analysis, the result of normality and homogeneity test of both group are having normal and homogeneous distribution. There is a significant effect of learning outcomes between students who were taught by using Questions Students Have learning methods and a group of students who were taught byÂ  using conventional methods. The mean score of students who are taught by using conventional learning method is 26.63 with a standard deviation of 3.63 and the mean score of students who are taught by using Questions Students Have learning methods is 32.88 with a standard deviation of 3.84. This shows that the students who are taught by using Questions Students Have learning methods have higher learning outcomes than conventional learning methods.